Faire face aux tensions liées à la reconfiguration du système universitaire italien : la voix des professeurs(es) - Fabrizio Chello (Recherches en Éducation)
The reconfiguration of University system is an international phenomenon of profound relevance. This is composed by several changes relating to everyday practices acted by the actors (professors, students, technical-administrative staff, etc.) who inhabit this context. Among these changes, the paper focuses on the transformations of professional agency of university professors – with particular attention to activities of research, teaching and governance – through the analysis of the results of a research conducted at Suor Orsola Benicasa University of Naples. Based on a comprehensive epistemological and methodological posture, the research was articulated in two successive phases. A first exploratory phase aimed to specify the research questions, to choose the field of investigation, to elaborate anchored hypotheses and to construct the methodological tools for the empirical investigation. The second phase, making use of semi-structured interviews, aimed to bring out and deconstruct the dominant representations of professional action. The results show that, in order to face with the tensions associated with the reconfiguration of the Italian university system, professors switch between different action grammars.